Team training and assessment in mixed reality-based simulated operating room: Current state of research in the field of simulation in spine surgery exemplified by the ATMEOS project Teamtraining und Assessment im Mixed-reality-basierten simulierten OP: Aktueller Stand der Forschung im Bereich Simulation in der Wirbelsäulenchirurgie am Beispiel des Projekts ATMEOS - Stefan, R.; Pfandler, Michael; Wucherer, R.; Habert, S.; Fuermetz, J.; Weidert, S.; Euler, E.; Eck, Ulrich; Lazarovici, M.; Weigl, M.; Navab, N. (Unfallchirurg, 2018)
Surgical simulators are being increasingly used as an attractive alternative to clinical training in addition to conventional animal models and human specimens. Typically, surgical simulation technology is designed for the purpose of teaching technical surgical skills (so-called task trainers). Simulator training in surgery is therefore in general limited to the individual training of the surgeon and disregards the participation of the rest of the surgical team. The objective of the project Assessment and Training of Medical Experts based on Objective Standards (ATMEOS) is to develop an immersive simulated operating room environment that enables the training and assessment of multidisciplinary surgical teams under various conditions. Using a mixed reality approach, a synthetic patient model, real surgical instruments and radiation-free virtual X‑ray imaging are combined into a simulation of spinal surgery. In previous research studies, the concept was evaluated in terms of realism, plausibility and immersiveness. In the current research, assessment measurements for technical and non-technical skills are developed and evaluated. The aim is to observe multidisciplinary surgical teams in the simulated operating room during minimally invasive spinal surgery and objectively assess the performance of the individual team members and the entire team. Moreover, the effectiveness of training methods and surgical techniques or success critical factors, e. g. management of crisis situations, can be captured and objectively assessed in the controlled environment.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Clinical competence; Education; medical; Educational measurement; Multidisciplinary operating room team; Skills